2021
DOI: 10.3390/plants10040614
|View full text |Cite
|
Sign up to set email alerts
|

Rootstocks with Different Vigor Influenced Scion–Water Relations and Stress Responses in AmbrosiaTM Apple Trees (Malus Domestica var. Ambrosia)

Abstract: In recent years, awareness has been raised around the benefits of diversifying rootstocks, in order to enhance tree health and sustain apple fruit production under the influence of climate change. However, performances of many rootstocks under stresses remain unclear. This study aimed to set the first step towards a much-needed comprehensive evaluation on water relationships and stress responses of scion–rootstock systems for the popular apple cultivar AmbrosiaTM (Malus domestica var. Ambrosia), because its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The midday stem water potential measured in this well irrigated orchard ranged from -0.87 to -0.98 MPa (Table 1). These observations follow similar patterns observed for different rootstocks in apple (Sarita et al, 2013;Xu et al, 2021) has been previously reported for apple rootstocks. Like stem length, stem water potential was the lowest for M.9.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The midday stem water potential measured in this well irrigated orchard ranged from -0.87 to -0.98 MPa (Table 1). These observations follow similar patterns observed for different rootstocks in apple (Sarita et al, 2013;Xu et al, 2021) has been previously reported for apple rootstocks. Like stem length, stem water potential was the lowest for M.9.…”
Section: Discussionsupporting
confidence: 91%
“…Rootstocks can also be used to improve water and nutrient uptake (Tworkoski and Fazio, 2015), reduce disorders (Blanco et al; unpublished) contributing to enhanced economic and environmental sustainability. Although dwarfing has been extensively characterized in different apple cultivars, the underlying physiological mechanisms contributing to this dwarfing effect remain unclear (Simon and Chu, 1984;Marguerit et al, 2012;Foster et al, 2017;Xu and Ediger, 2021). Some theories attribute the dwarfing mechanism of rootstocks to changes to the supply of water from the rootstock to the scion (Atkinson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural Research and Extension Center (AREC) in Winchester, VA, the United States (39.11, −78.28) were used. It is worth noting that B.9 and M.9 rootstocks have similar vigor and previous reports showed no significant differences between these rootstocks in stress tolerance [50] and bud break [51]. Three trees from each cultivar were randomly selected, each considered as a biological replicate.…”
Section: Plant Materials and Samples Preparationmentioning
confidence: 99%
“…Information about the water status of fruit crops is necessary when planning an irrigation program that will reliably ensure the optimal functioning of physiological indicators. However, at the same time, there is no consensus on a suitable indicator on this issue and the topic remains debatable [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%